Scripting language framework in solving Facility Layout Problem (FLP) based on meta-heuristics hybridization / Suraya Masrom … [et al.] - Masrom, Suraya; Ahmad, Normah; Omar, Nasiroh; Abd Rahman, Abdullah Sani (Universiti Teknologi MARA, Perak, 2018)
Facility layout can be seen everywhere in people’s daily life and industry so that it has a broad research background, which returns the economic and social benefits. Besides time critical, another challenge of creating a facility layout is to resolve dynamic factors, such as the modification of building layout and the placement of new elements in the layout. Users may rely on computerized facility layout, but when involves with dynamic factors, a great deal of technical hurdles appears mainly in the computer programming. Therefore, this research proposes an easy programming approach to solve facility layout problem with meta-heuristics algorithm in a scripting language software framework. Evaluation results indicated that the codes of the scripting language are simpler and concisely describe the algorithms in a directly publishable form.